Nutrisi, Narasi, dan Negosiasi Risiko: Membaca Kontroversi MBG dalam Perspektif Risk Communication: Nutrisi, Narasi, dan Negosiasi Risiko: Membaca Kontroversi MBG dalam Perspektif Risk Communication - Suryani Musi; Dea Audia Elsaid (Journal of Media and Communication Studies, 2026)
This study examines the controversy surrounding Indonesia's Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) from a risk communication perspective. Normatively, MBG is presented as a strategic intervention to reduce stunting and improve human capital. In practice, however, the program has become a contested public narrative shaped by food safety concerns, fiscal scale, media framing, and institutional trust. Using qualitative conceptual analysis based on crisis communication, risk communication, and risk society literature, this article explains the gap between objective risk and perceived risk in public responses to MBG. The findings show that public anxiety is not caused solely by operational problems, but by the failure of policy communication to acknowledge uncertainty transparently and consistently. Statistical claims on stunting reduction do not automatically produce legitimacy because citizens evaluate risk through emotion, social value, experience, and trust. MBG therefore shifts from a technical nutrition policy into a narrative crisis of state credibility.